Comparing TOEFL and teacher’s assessment scores in measuring student’s English skills - Hutabarat, Pritz (Journal of English Education and Teaching, 2023)
Standardized English tests have long been used to determine English learner’s level of proficiency. Tests such as TOEFL (Test of English as a foreign language) and IELTS (International English language testing system) are arguably the most popular English tests in the world. On the other hand, English learners are consistently being assessed by their teachers through a performance-based assessment which provides a comprehensive description of student’s learning achievement in learning English. The results of these two forms of assessments were hardly compared and correlated. Therefore, this paper investigates the correlation between student’s TOEFL score and teacher score. Moreover, this study explores how teacher uses washback effects of TOEFL and class tests. Investigating 42 grade 12 students in an English immersion school in Indonesia, the result of this study indicated a positive but weak correlation between TOEFL and teacher’s assessment scores (r = 0.246, p = 0.116). This weak correlation indicates that the two types of assessments measure student’s achievement and performance differently. The washback effect of TOEFL is mainly in the form of teacher’s encouragement to the students to be more serious when taking TOEFL test so that they will be about to get higher scores.